Bis[cyclic (alkyl)(amino)carbene] isomers: Stable trans-bis(CAAC) versus facile olefin formation for cis-bis(CAAC). Issue 45 (18th May 2022) - Puerta Lombardi, Braulio M.; Pezoulas, Ethan R.; Suvinen, Roope A.; Harrison, Alexander; Dubrawski, Zachary S.; Gelfand, Benjamin S.; Tuononen, Heikki M.; Roesler, Roland
Abstract : A trans -bis(CAAC) was isolated and shown to be a ditopic ligand for rhodium and iridium. The cis- isomer is unstable towards intramolecular CC-bond formation, however, its formal insertion products into the bonds of H2 O and NH3 were identified. Abstract : Isomeric bis(aldiminium) salts with a 1, 4-cyclohexylene framework were synthesized. The first isolable bis(CAAC) was prepared from the trans -stereoisomer and its ditopic ligand competency was proven by conversion to iridium(i ) and rhodium(i ) complexes. Upon deprotonation, the cis -isomer yielded an electron rich olefin via a classic, proton-catalyzed pathway. The CC bond formation from the desired cis -bis(CAAC) was shown to be thermodynamically very favorable and to involve a small activation barrier. Compounds that can be described as insertion products of the cis -bis(CAAC) into the E–H bonds of NH3, CH3 CN and H2 O were also identified.